2001
DOI: 10.2307/3090189
|View full text |Cite
|
Sign up to set email alerts
|

Birth Weight and Income: Interactions across Generations

Abstract: This paper attempts to answer a series of questions regarding the interaction of income and birth weight across generations. First, does the effect of the income of a mother during her pregnancy on her infant's birth weight depend on the family's birth weight history (genetic predisposition)? Second, does the effect of low birth weight status on adult life chances depend on income during early childhood? These questions have implications for the way we envision the biological and social worlds as interacting a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
60
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 48 publications
2
60
0
2
Order By: Relevance
“…The pattern of profile of baby weight by mother's occupation brought to light equivalent average change of the baby weights. Occupation in the analysis was not significant confirming Conley & Bennett (2000) findings that no occupational income or education has effects on the probability of low birth weight among infants. The profile of baby weights by mother's parity group showed that mothers who gave birth up to two-three times had the best mean change in weights of babies compared to those who gave birth once as well as those who had four -five number of births which was the least.…”
Section: Discussionsupporting
confidence: 57%
“…The pattern of profile of baby weight by mother's occupation brought to light equivalent average change of the baby weights. Occupation in the analysis was not significant confirming Conley & Bennett (2000) findings that no occupational income or education has effects on the probability of low birth weight among infants. The profile of baby weights by mother's parity group showed that mothers who gave birth up to two-three times had the best mean change in weights of babies compared to those who gave birth once as well as those who had four -five number of births which was the least.…”
Section: Discussionsupporting
confidence: 57%
“…Others have suggested that the influence of birth weight may be graded by other indicators of family background and experiences (as noted in Hack et al, 1995). For example, Conley and Bennett (2001) reported mixed evidence that birth weight and income interact (see also Conley et al, 2007). We found few (and no robust) indications that the influence of birth weight on both cognitive development and timely high school completion varies according to family income early in children's lives, the early home environment, whether the child is female, family structure, the mothers age at birth, race/ethnic background, maternal AFQT, or cognitive development growth with respect to high school completion.…”
Section: Discussionmentioning
confidence: 99%
“…Although the data suggesting that birth weight is moderated by family circumstances is sparse (e.g., Lin et al, 2007;Conley and Bennett, 2001;Currie and Hyson, 1999;Hack et al, 1995), research with large samples and sufficient statistical power are relatively rare in birth weight moderation studies. Conley and colleagues (2007), using the PSID-CDS, for example, report that birth weight is related to achievement for black siblings and siblings with a mother with less than a high school education.…”
Section: The Role Of Family Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Socioeconomic advantage has been shown to buffer adverse effects of certain exposures, low birth weight is a much explored example. [25][26][27] However, whether this holds true for adult exposures remains little explored. SES is known to be associated with cognitive function 28 and with IMT and its progression over time.…”
Section: Introductionmentioning
confidence: 99%